4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Regulation of casein micelles dissociation by sodium tripolyphosphate to improve gel properties as stabilizers and protein fortifier for high-protein yogurt - Zi-Ying Zhao; Zi-Wei Liu; Bo-Kang Yu; Ying-Chao Qiu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Exploring immunomodulatory peptides derived from bovine colostrum protein based on QSAR models: preparation, identification, in vitro activity, and molecular docking analysis - Ying-Chao Qiu; Zi-Ying Zhao; Stella Zhu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Sulfuric acid-induced microphase separation strengthens poly(acrylic acid) hydrogels - Zheng Luo; Yuan Feng; Meng Mu; Xing Zhang; Heng Liu; Mingmin Zhang; Xin Su; Yujun Feng (Chemical Engineering Journal, 2026)

Low-temperature thermochemical energy storage behavior of Zn-doped phosphogypsum-based calcium sulfate dihydrate: Correlating defect evolution with electronic structure - Fei Mu; Shuai Luo; Meng Fu; Yuanyuan Li; Xuyuan Tang; Yaoqi Huang; Xiaomin Cheng (Chemical Engineering Journal, 2026)

Neural and metabolic mechanisms of emetogenic foodborne toxins via the brain-gut axis in ageing and cachexia - Hao Xu; Muying Li; Yuting Liu; Guanghui Nie; Mu Li; Zitong Meng (Toxicon, 2026)

Trophic strategies of sympatric carnivorous fishes under off-seasonal water-level regulation in Hongze Lake - Si Luo; Zhen Zhang; Dangen Gu; Qiujing Zhu; Huan Mu; Meng Wang; Ruiqiong Zhang; Shiyu Jin (Limnologica, 2026)

Limited enzymatic hydrolysis reshapes whey protein antigenicity, taste profile, and techno-functional properties - Meng-Qi Liu; Wen-Qi Liang; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Sustainable high internal phase emulsions based on millet bran nanocellulose and EGCG: Centrifugal fabrication, antioxidant reinforcement, and 3D printability - Mo Chen; Yu-hao Wu; Xu Guo; Jin-yue Sun; Nan Chen; Mu-xuan Wang; Qi-dong Ren; Mohamed A. Farag; Nilufar Z. Mamadalieva; Min Wang; Meng-qi Zhang; Chao Liu (Food Chemistry, 2026)

Unraveling health disparities across cause-specific outcomes associated with emerging air pollutants: Evidence on black carbon and ultrafine particles in Buffalo, New York - Xuewen Pei; Muwu Xu; Harshita Sharma; Marina Oktapodas Feiler; Riana R. Pryor; Lina Mu; Meng Wang (Environmental Research, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Cooking water quality shapes the flavor, texture, and pasting properties of foxtail Millet: Associations with key water ions - Yiru Zhang; Pengyu Tian; Canran Zhang; Tingting Mu; Jun Zhang; Xiaodong Liu; Zhilong Meng (Journal of Cereal Science, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Functional whey protein nanofibrils: A promising fat substitute for improving quality characteristics of the low-fat sour cream - Yuxuan Huang; Han Wang; Huaijie Zhang; Yifei Meng; Zhanmei Jiang; Zhishen Mu (Innovative Food Science & Emerging Technologies, 2026)

Effect of pile corner rounding on local scour around offshore wind turbine foundations in sands using CFD–DEM - Xiangyi Meng; Yifan Lu; Xiaoming Feng; Guizhong Tian; Yadong Zhu; Zhongqiu Mu (Computers and Geotechnics, 2026)

The transformation of Ca/Mg-silicate to Co/Ni/Fe-silicate in biomass carbon from gourd leaves for supercapacitors - Shaoqing Zhang; Xiang Ke; Tianming Lv; Jiqi Zheng; Yang Mu; Xuchun Wang; Miao Cui; Teng Du; Changgong Meng (Chemical Engineering Journal, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

A systematic identification and characterization of long noncoding RNAs during abiotic stress in Medicago truncatula - Kanghua Du; Yingan Zhu; Weiyu Yan; Ting Gao; Wanfu Mu; Ziwei Zhao; Zhong Dan; Xiaolu Meng; Haoting Chen; Yan Zhao; Jie Zhang (Journal of Plant Physiology, 2026)

Heteroaggregation with microalgae masks charge-dependent accumulation but amplifies charge-dependent toxicity of nanoplastics in mussels - Fangli Wu; Yuqing Deng; Quanying Wu; Hongxing Chen; Jingli Mu; Yuting Zhang; Wei Meng; Ning Li; Lingtian Xie (Journal of Hazardous Materials, 2026)

Differentiated mechanisms of microplastic accumulation and migration in lakes, wetlands and reservoirs: A comparative study of three ecosystem types in the North China Plain - Guangyin Sun; Siyu Hao; Xin Meng; Xinyu Cao; Yongchao Mu (Journal of Environmental Chemical Engineering, 2026)

Hybrid energy system based on co-firing municipal sludge coupled with power generation: energy balance, carbon emissions, and thermo-economic analysis - Zhaolei Meng; Zongguo Wen; Xin Meng; Fan Fei; Yanfei Mu; Gang Li; Tao Zhou; Quanjie Li; Yiqun Meng (Journal of Cleaner Production, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Roles of ACSL6 in lipid homeostasis and stress responses in the nervous system - Shaoyang Zhang; Fangyu Meng; Yuhang Yuan; Hongyu Xiong; Faqin Mu; Xiang Li; Lingqiao Wu; Xiaopeng Yang; Xingyu Li; Yizhe Mu; Ceshi Chen; Huixin Wu; et al. (Metabolic Brain Disease, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Staphylococcus haemolyticus isolated from the Elaphurus davidianus: Pathogenicity and antimicrobial susceptibility profile - Yongcheng Meng; Qingyan Han; Mengling Han; Zhenpeng Li; Jie Wang; Sihan Zuo; Zhen Huang; Qian Mu; Yongli Hua; Wanling Yao; Wangdong Zhang (Research in Veterinary Science, 2026)

IgG release and peptides production by trypsin-driven selective hydrolysis of casein in bovine colostrum to improve immunomodulatory activity - Ying-Chao Qiu; Meng-Jiao Wang; Zi-Ying Zhao; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Identification of conserved vaccine targets in Mycoplasma bovis through integrated pan-genome and reverse vaccinology approaches with in vivo immunogenicity and safety evaluation - Jiaming Mu; Zhongmei Ma; Jie Li; Xuepeng Cai; Qingling Meng; Jun Qiao (The Veterinary Journal, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Layered double hydroxides vs. metal-organic frameworks: Which enables more sustainable phosphate fertilizer production from sludge? - Xiaole Wang; Qian Zhao; Xiaoxiang Cheng; Jingtao Xu; Shujuan Meng; Yifan Zhao; Kechao Han; Ruimin Mu; Lei Liu (Journal of Environmental Chemical Engineering, 2026)

Tamarisk miRNA target genes TcSPL5 and TcNAC1 mediate the post-transcriptional responses of salt stress - Yang Zheng; Junwen Wang; Meng Xu; Mu Cao; Shaoyan Jiang; Jianwen Wang; Li-an Xu (Plant Science, 2026)

The synergistic effect of algal-bacterial granular sludge in a sequencing batch reactor with tetracycline-containing synthetic livestock and poultry breeding wastewater - Yuanda Du; Shoubo Zhao; Yanan Gao; Yujie Yan; Yi Kong; Wenwen Meng; Xinru Lu; Shun Zheng; Haolin Mu; Xiaojing Chen; Qiang Kong (Journal of Environmental Management, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Denitrification driven by varying concentrations of Mn (II) under no external carbon source conditions: Denitrification performance, nitrogen transformation and metabolic pathways - Lingyun Mu; Xiaoxiao Hou; Xinshan Song; Xiangzhou Meng; Dong An (Bioresource Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Enzymatic hydrolysis of bovine casein assisted by microfluidization: Effects on functional properties and identification of anxiolytic peptides - Meng-Jiao Wang; Zi-Ying Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Enhanced performances of iron-rich sludge ash for chemical looping gasification of pretreated rice straw by the modification of transition metal oxides - Ying Dai; Jinpeng Jiang; Xiran Xu; Meng Sun; Xiaoyuan Wang; Lin Mu; Jianbiao Chen; Yuezhao Zhu; Jinzhu Tan (Fuel, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Impacts on the maximum lateral deflection and adjacent shield tunnels from the ground stiffness of an excavation - Fan-Yan Meng; Bo Hu; Mu-Chun Liu; Bin-Chen Benson Hsiung; Muhammad Dwiyanto Agung Prakasa (Tunnelling and Underground Space Technology, 2026)

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Integrated surface-enhanced Raman spectroscopy and machine learning for identification and quantification of multi-target pesticide residues in fruit juices - Shen Jiang; Qiuyun Li; Xubin Quan; Yaowen Xing; Yujiang Huang; Xuming Mu; Yitong Meng; Guangrun Wu; Tong Ju; Yuhan Chu; Ruiyao Ma; Jing Wu; et al. (Food Chemistry, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Transcriptome-wide identification of glycoRNAs by Clier-seq pipeline - Nannan Zhu; Yan-Lin Yang; Yuan-Tao Liu; Zheng-Zhou Lu; Yan Wang; Yi-Ling Luo; Ning Meng; Yan Yuan; Qian Zhong; Mu-Sheng Zeng (Science China Life Sciences, 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

Design of Sn-doped MoS2 piezocatalyst for high-efficiency antibiotic degradation: mechanism and performance - Mingyang Xu; Xiang Wang; Jingyu Yu; Zhenlin Mu; Shengjun Yang; Chenxi Guo; Guoxuan Li; Yinglong Wang; Fanqing Meng (ENGINEERING Environment, 2026)

Ground validation of dust multi-properties analyzer onboard Tianwen-2 - Xu Tan; Cunhui Li; Jiajie Wang; Zhongcheng Mu; Zecheng Cui; Meng Chen; Xin Ren; Xiaodong Liu; Yan Su; Wei Wang; Renhao Tian; Jiawei Li (Advances in Space Research, 2026)

Aerodynamic performance degradation of offshore wind turbine blades under icing with varying angles of attack - Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Senlin Mu; Fanting Kong; Bin Zhang; Xiangyi Meng (Ocean Engineering, 2025)

Effects of roasting on the quality characteristics, sensory profiles, and volatile flavor compounds of different cuts of Yanbian yellow beef - Bowen Qin; Xiangji Meng; Rufeng Lian; Jinlong Tan; Chunxiang Piao; Juan Wang; Hongmei Li; Changcheng Zhao; Baide Mu; Guanhao Li (International Journal of Gastronomy and Food Science, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

In-situ layer-by-layer reaction method for preparing thermochromic K2O·nSiO2-based anti-fire glass - Yuanchun Mu; Yuran Qiao; Zongpu Yang; Tiantian Meng; Xiaoyu Li (Energy and Buildings, 2025)

Isopropanol gas sensor based on CoSnO3/SnO2/Zn2SnO4 ternary heterostructure with high response - Fangling Zhou; Zhuangzhuang Mu; Gaoliang Chen; Zhenyu Yuan; Renze Zhang; Xin Yan; Fanli Meng (Chemical Engineering Journal, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Efficient peroxymonosulfate activation by γ-Al2O3 nanosheets supported FeS2 for neonicotinoids removal: Role of surface hydroxyl-enhanced activation and sulfur-facilitated iron redox cycling - Zhiqiang Xu; Meng Zhang; Hongxin Mu; Simin Li; Yuanqing Bu; Houhu Zhang (Chemical Engineering Journal, 2025)

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Dual-lanthanide functionalized hydrogen-bonded organic frameworks for fluorescent detection of quinolone antibiotics in multi-media - Shuang Meng; Bofang Mu; Shun Mao; Zhuo Li (Journal of Hazardous Materials, 2025)

Correlations and analysis of heat transfer coefficient for seawater falling film evaporation on horizontal tube - Qiang Meng; Shengqiang Shen; Chao Li; Di Wang; Xingsen Mu (Desalination, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

DEM-DDM study on the humidification uniformity of brown rice in a pan coater - Xiangyi Meng; Yadong Zhu; Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Bin Zhang; Yongsheng Pei; Yifan Lu (Biosystems Engineering, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Experimental study on the purification performance of sterilization-Trombe walls with and without fins in the heating season - Hongju Meng; Jie Ji; Hao Xie; Hengmin Jia; Yu Qian; Jiyao Li; Yan Mu (Building and Environment, 2025)

Study on new method of freezing–thawing water replenishment and its mechanical properties for seasonally frozen soil - Miao Wang; Yanxiu Guo; Shangjiu Meng; Anshuang Su; Hailong Mu; Mingwei Hai (Acta Geophysica, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Photo-depositing ruthenium species on defect-rich strontium titanate enhances photothermal catalytic dry reforming of methane through light-induced charge transfer and oxygen migration - Zhiyong Tu; Chunxia Mu; Xiangchao Meng; Zhangfa Tong; Kelei Huang (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Development of colloidal gold test strip based on the BsVg819 gene fragment of vitellogenin of Bostrichthys sinensis for the detection of vitellogenin in multiple fish species - Jiahang Mu; Tingting Zhou; Kun Meng; Yangyang Zhang; Junhua Fang; Kefu Zhou (Fish Physiology and Biochemistry, 2025)

Development of a colloidal gold immunochromatographic strip for the rapid on-site detection of Ecytonucleospora hepatopenaei (EHP) - Xianzhi Meng; Yixiang Yu; Dandan Ma; Mingxin Mu; Quan Sun; Quanlin Liu; Xiaodong Fan; Tian Li; Jie Chen; Guoqing Pan; Zeyang Zhou (Journal of Invertebrate Pathology, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

An overview of the chirality of diet-related fatty acids, glycerolipids, and glycerophospholipids - Shu-tao Sun; Yan-jie Jiang; Xu Guo; Meng-qi Zhang; Qi-dong Ren; Jesus Simal-Gandara; Mu-xuan Wang; Xiao-jia Xue; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2025)

The impact of organic loading rate on the cultivation and stability of aerobic granular sludge in continuous flow reactor - Yingjian Zhang; Fanchao Meng; Zehan Huang; Minghui Liu; Xuegang Mu; Xuelong Zhang; Guilherme Lelis Giglio; Zhaoxu Peng (International Biodeterioration & Biodegradation, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Structure-selectivity relationship of anion exchange resins with different quaternary amine functional groups for highly selective removal of PFAS from chromium-plating wastewater - Xiangzhe Jiang; Yihua Luo; Shuang Mu; Bojiang Meng; Wei Wang; Gang Yu; Shubo Deng (Water Research, 2025)

CdS/NiCoAl-LDH heterojunction for superior photocatalytic hydrogen production and stability in water splitting - Ruimin Yang; Wenning Mu; Longyan He; Junjin Meng; Xiaolong Bi; Wenbin Luo; Shaohua Luo; Xuefei Lei (Chemical Engineering Journal, 2025)

Development and experimental validation of a thermal inactivation model for airborne bacteria and its application in Trombe wall systems - Hao Xie; Hengmin Jia; Jie Ji; Yu Qian; Hongju Meng; Jiyao Li; Yan Mu (Building and Environment, 2025)

Performance investigation of multi-functional series-connected building-integrated photovoltaic/thermal system and analysis of its multi-objective optimization design strategy - Yu Qian; Jie Ji; Hao Xie; Hengmin Jia; Hongju Meng; Jiyao Li; Yan Mu (Building and Environment, 2024)

Recent progress in fucosylated derivatives of lacto- N -tetraose and lacto- N -neotetraose - Longhao Yang; Yingying Zhu; Jiawei Meng; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Sub-chronically exposing zebrafish to environmental levels of methomyl induces dysbiosis and dysfunction of the gut microbiota - Mingxiao Li; Xi Chen; Chao Song; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (Environmental Research, 2024)

Modification of Prussian blue analogues as high-performance cathodes for sodium-ion batteries - Yifan Huang; Wenning Mu; Junjin Meng; Xiaolong Bi; Xuefei Lei; Shaohua Luo (Chemical Engineering Journal, 2024)

Performance analysis of a novel air filtration and sterilization PV-Trombe wall - Hao Xie; Hengmin Jia; Jie Ji; Yu Qian; Hongju Meng; Jiyao Li; Yan Mu (Building and Environment, 2024)

S2CPL: A novel method of the harvest evaluation and subsoil 3D cutting-Point location for selective harvesting of green asparagus - Si Mu; Nianzu Dai; Jin Yuan; Xuemei Liu; Zhenbo Xin; Xiangbao Meng (Computers and Electronics in Agriculture, 2024)

Boosting solvent resistance and structure stability of degradable polyester through extended-chain crystal structure: A preliminary case of oil/water separation membrane - Jia-Yao Chen; Na Li; Siyang Wang; Tian-Yu Wu; Xiaoyu Meng; Hai-Mu Ye (Journal of Environmental Chemical Engineering, 2024)

Characterization of SCOBY-fermented kombucha from different regions and its effect on improving blood glucose - Yang Meng; Xueqi Wang; Yunjuan Mu; Maozhen Zhao; Yujia Liu; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Bioscience, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

The influence of North Atlantic sea surface temperature fluctuations on the climate of the Qinling-Bashan Mountains, China based on a 250 year tree-ring record - Qiufang Cai; Mei Xie; Yu Liu; Congxi Fang; Zhixin Hao; Meng Ren; Qiuyue Zhou; Yikui Mu; Yufei Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Interfacial dynamic adsorption behaviour of the bovine alpha- Lactalbumin at the oil-water interface: Evaluating the role of glycyrrhizin - Ruijie Shi; Zengli Gao; Meng Li; Zhanmei Jiang; Zhishen Mu (Food Hydrocolloids, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Future trends in the field of Pickering emulsions: Stabilizers, spray-dried microencapsulation and rehydration for food applications - Weihao Meng; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Trends in Food Science & Technology, 2024)

Multidimensional occurrence and diet risk of emerging contaminants in freshwater with urban agglomerations - Tingting Chai; Yinyin Jin; Feng Cui; Zongjie Li; Mingxiao Li; Shunlong Meng; Lilai Yuan; Jing Qiu; Jiandong Mu; Guohua Xiao; Xiyan Mu; Yongzhong Qian (Journal of Hazardous Materials, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

The giant African snail, Lissachatina fulica (Bowdich, 1822) in China: current status, threats and management - Wen Xiong; Qian Guo; Miao Fang; Meng Xu; Xidong Mu (Molluscan Research, 2024)

Investigation on the operating capacity expansion through parallel schemes of reciprocating-switcher energy recovery device for desalination: Simulation, verification and parameterization - Jie Zhou; Dong Liu; Qinghong Zhang; Chao Bian; Xiuxia Meng; Naitao Yang; Shichen Mu (Desalination, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Tyrosine kinase inhibitor–induced hypothyroidism: mechanism and clinical implications - Zhipeng Wang; Hongsen Wang; Chen Bu; Bosu Meng; Yuhui Mu; Shouhong Gao; Wansheng Chen; Xia Tao (European Journal of Clinical Pharmacology, 2024)

Test and application of abrasion characteristics of brown rice - Xiangyi Meng; Yadong Zhu; Fuguo Jia; Guizhong Tian; Xiaoming Feng; Yongsheng Pei; Zhongqiu Mu (Innovative Food Science & Emerging Technologies, 2024)

Landsat observations of total suspended solids concentrations in the Pearl River Estuary, China, over the past 36 years - Qiang Sun; Wei Luo; Xianzhang Dong; Shaohua Lei; Meng Mu; Shuai Zeng (Environmental Research, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Factors affect the oxygen production of Chlorella pyrenoidosa in a bacterial-algal symbiotic system: Light intensity, temperature, pH and static magnetic field - Shiyu Yin; Wenbiao Jin; Tingting Xi; Xu Zhou; Zhongqi He; Xuli Meng; Mu. Naushad; Guangming Jiang; Xuan Li (Process Safety and Environmental Protection, 2024)

β-lactoglobulin hydrolysates by L.plantarum AHQ-14 and L.bulgaricus BD0390 alleviate allergic responses to β-lactoglobulin in sensitized mice - Shujuan Jiang; Yutong Jiang; Lingying Meng; Yanfeng Tuo; Guangqing Mu (Food Bioscience, 2024)

Member separation and deformation recognition of spatial grid structures in-service - Mu-Nan Xu; Li-Min Sun; Yu-Fei Liu; Bao-Luo Li; Meng Zhou; Xuan Chen (Engineering Structures, 2024)

Association of prenatal exposure to PM2.5 and NO2 with gestational diabetes in Western New York - Kexin Zhu; Pauline Mendola; Vanessa M. Barnabei; Meng Wang; Rachael Hageman Blair; Joel Schwartz; James Shelton; Lijian Lei; Lina Mu (Environmental Research, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Rotenone impairs brain glial energetics and locomotor behavior in bumblebees - Jieteng Chen; Xiaohuan Mu; Huiling Liu; Qiyao Yong; Xiaoman Ouyang; Yan Liu; Li Zheng; Hao Chen; Yifan Zhai; Jie Ma; Liang Meng; Shanshan Liu; et al. (Science of The Total Environment, 2024)

Comprehensive understanding on sources of high levels of fine particulate nitro-aromatic compounds at a coastal rural area in northern China - Yueru Jiang; Xinfeng Wang; Min Li; Yiheng Liang; Zhiyi Liu; Jing Chen; Tianyi Guan; Jiangshan Mu; Yujiao Zhu; He Meng; Yang Zhou; Lan Yao; et al. (Journal of Environmental Sciences, 2024)

Significant enhancement of biomethane recovery in up-flow anaerobic sludge blanket reactor treating starch wastewater through oyster shells conditioning - Hui Mu; Qingyu Sun; Meng Zhong; Chunhui Zhao; Yongfang Zhang; Liguo Wang (Journal of Cleaner Production, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

The neurobehavioral impacts of typical antibiotics toward zebrafish larvae - Yining Zhang; Xue Li; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Guijie Hao; Xueping Ye; Shunlong Meng; Guohua Xiao; Jiandong Mu; Xiyan Mu; Jing Qiu; et al. (Chemosphere, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Extrusion for reducing malondialdehyde-induced whey protein isolate oxidation in relation with its physicochemical, functional and intro digestive properties - Zhanmei Jiang; Yifei Meng; Chenyue Hou; Munkh-Amgalan Gantumur; Yitong Gao; Yuxuan Huang; Siyuan Zhang; Yu Sun; Sukhbaatar Narantuya; Zhishen Mu; Juncai Hou (Food Hydrocolloids, 2023)

Assessing the timing and the duration of exposure to air pollution on cardiometabolic biomarkers in patients suspected of coronary artery disease - Kexin Zhu; Zhihui Hou; Conghong Huang; Muwu Xu; Lina Mu; Guan Yu; Joel D. Kaufman; Meng Wang; Bin Lu (Environmental Research, 2023)

Hydro-mechanical behavior of unsaturated intact paleosol and intact loess - Qingyi Mu; Longlong Meng; Zhao Lu; Limin Zhang (Engineering Geology, 2023)

Stress-dependent water retention behaviour of two intact aeolian soils with multi-modal pore size distributions - Q.Y. Mu; L.L. Meng; C. Zhou (Engineering Geology, 2023)

Electricity facilitates the lithium sorption from salt-lake brine by H3LiTi5O12 nanoparticles: Kinetics, selectivity and mechanism - Qiuyue Wang; Mu Li; Bing Zhao; Boyang Meng; Wutong Chen; Zekai Jiang; Xin He; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Recent advances in a functional deoxy hexose l-fucose: Occurrence, physiological effects, and preparation - Jiawei Meng; Yingying Zhu; Ningning Wang; Wenli Zhang; Wanmeng Mu (Trends in Food Science & Technology, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Effects of clay content on the desiccation cracking behavior of low-plasticity soils - Qingyi Mu; Longlong Meng; Yanqian Shen; Chao Zhou; Zhaolin Gu (Bulletin of Engineering Geology and the Environment, 2023)

Recent Advances in China on the Predictability of Weather and Climate - Wansuo Duan; Lichao Yang; Mu Mu; Bin Wang; Xueshun Shen; Zhiyong Meng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2023)

Impacts of site real-time adaptive control of water-sensitive urban designs on the stormwater trunk drainage system - Xuli Meng; Xuan Li; Allan Charteris; Zhenyao Wang; Mu. Naushad; Long D. Nghiem; Huan Liu; Qilin Wang (Journal of Water Process Engineering, 2023)

Obtaining mutant Chlorella vulgaris strains with excellent self-flocculation properties and high wastewater treatment efficiency via atmospheric and room temperature plasma technique - Guixia Ma; Qianya Meng; Ruimin Mu; Feng Qi; Xihan Wang (Journal of Water Process Engineering, 2023)

A biomimetic mineralization nanosystem based on glycolysis-oxidative stress-autophagy regulation for the suppression of malignant tumor and lung metastasis - Ping Guan; Zhaoxu Meng; Xinran Liu; Jiaxiang Mu; Zichun Gao; Xinrong Yu; He Lian (Chemical Engineering Journal, 2023)

A new and simple method for predicting the collapse susceptibility of intact loess - Q.Y. Mu; B.L. Dai; C. Zhou; L.L. Meng; J.G. Zheng; J.W. Zhang; Y.T. Yu; Z.H. Liu (Computers and Geotechnics, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Organic matter accumulation mechanisms in the Wufeng-Longmaxi shales in western Hubei Province, China and paleogeographic implications for the uplift of the Hunan-Hubei Submarine high - Shizhen Li; Zhi Zhou; Haikuan Nie; Mu Liu; Fanyang Meng; Bin Shen; Xiaotao Zhang; Siyu Wei; Zhaodong Xi; Shousong Zhang (International Journal of Coal Geology, 2023)

Dough rheological properties, texture, and structure of high-moisture starch hydrogels with different potassium-, and calcium-based compounds - Hong-Yuan Zhang; Hong-Nan Sun; Meng-Mei Ma; Tai-Hua Mu (Food Hydrocolloids, 2023)

An efficient green-emitting quantum dot with near-unity quantum yield and suppressed Auger recombination for high-performance light-emitting diodes - Xiaokun Fan; Zhen Mu; Zhao Chen; Yunfeng Zhan; Fanyuan Meng; Yang Li; Guichuan Xing; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

Chemical speciation and bioavailability of potentially toxic elements in surface sediment from the Huaihe River, Anhui Province, China - Mu You; Yunhu Hu; Ying Meng (Marine Pollution Bulletin, 2023)

Insight into comparison of binding interactions and biological activities of whey protein isolate exposed prior to two structurally different sterols - Meng Li; Jinzhe Li; Yuxuan Huang; Zengli Gao; Zhanmei Jiang; Zhishen Mu (Food Chemistry, 2023)

Bifunctional electrocatalyst junction engineering: CoP nanoparticles in-situ anchored on Co3(Si2O5)2(OH)2 nanosheets for highly efficient water splitting - Yang Mu; Yifu Zhang; Ziyi Feng; Xueying Dong; Xuyang Jing; Xiaoyu Pei; Yunfeng Zhao; Zongkui Kou; Changgong Meng (Chemical Engineering Journal, 2023)

Chitosan-based Pickering emulsion: A comprehensive review on their stabilizers, bioavailability, applications and regulations - Weihao Meng; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Carbohydrate Polymers, 2023)

Extraction, purification, chemical characterization and antioxidant properties in vitro of polyphenols from the brown macroalga Ascophyllum nodosum - Weihao Meng; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2023)

Quantitative transport and immobilization of cadmium in saturated-unsaturated soils with the combined application of biochar and organic fertilizer - Zhuowen Meng; Shuang Huang; Wenting Mu; Jingwei Wu; Zhongbing Lin (Environmental Science and Pollution Research, 2023)

Does foreign direct investment promote environmental performance: An investigation on shadow prices of pollutants - Ziming Yue; Lingyu Meng; Yunguo Mu; Tomas Baležentis; Zhiyang Shen (Journal of Cleaner Production, 2023)

Core-shell structural vanadium Oxide/Polypyrrole anode for aqueous Ammonium-Ion batteries - Xinjian Mu; Yu Song; Zengming Qin; Jianming Meng; Zhihui Wang; Xiao-Xia Liu (Chemical Engineering Journal, 2023)

Structure engineering of Mn2SiO4/C architecture improving the potential window boosting aqueous Li-ion storage - Xueying Dong; Yang Mu; Liuxue Shen; Haowei Wang; Chi Huang; Changgong Meng; Yifu Zhang (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Pickering emulsions with chitosan and macroalgal polyphenols stabilized by layer-by-layer electrostatic deposition - Weihao Meng; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Carbohydrate Polymers, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Benthic Sargassum composition and community characteristics in the intertidal zone of Hainan Island, China - Xiaoxiao Zou; Tian Meng; Dandan Yao; Zuo Chen; Jun Zhu; Dan Mu; Shixiang Bao (Marine Biology Research, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Exotic fishes that are phylogenetically close but functionally distant to native fishes are more likely to establish - Meng Xu; Shao‐peng Li; Jaimie T. A. Dick; Dangen Gu; Miao Fang; Yexin Yang; Yinchang Hu; Xidong Mu (Global Change Biology, 2022)
Since Darwin's time, degree of ecological similarity between exotic and native species has been assumed to affect the establishment success or failure of exotic species. However, a direct test of the effect of exotic–native similarity on establishment of exotics is scarce because of the difficulty in recognizing failures of species to establish in the field. Here, using a database on the establishment success and failure of exotic fish species introduced into 673 freshwater lakes, we evaluate the effect of similarity on the establishment of exotic fishes by combining phylogenetic and functional information. We illustrate that, relative to other biotic and abiotic factors, exotic–native phylogenetic and functional similarities were the most important correlates of exotic fish establishment. While phylogenetic similarity between exotic and resident fish species promoted successful establishment, functional similarity led to failure of exotics to become established. Those exotic species phylogenetically close to, but functionally distant from, native fishes were most likely to establish successfully. Our findings provide a perspective to reconcile Darwin's naturalization conundrum and suggest that, while phylogenetic relatedness allows exotic fish species to pre‐adapt better to novel environments, they need to possess distinct functional traits to reduce competition with resident native fish species.

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Synthesis of Fe3O4@Phoslock® composites and the application in adsorption of phosphate from aqueous solution - You Mu; Wuhui Luo; Zanpeng Cui; Meng Zhang; Philip Antwi; Dachao Zhang; Sili Ren (Environmental Science and Pollution Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Analysis of the microseismicity characteristics in landslide dam failure flume tests: implications for early warning and dynamics inversion - Yunpeng Yang; Guan Chen; Xingmin Meng; Shiqiang Bian; Yan Chong; Wei Shi; Wanyu Jiang; Jiacheng Jin; Chen Li; Xinliang Mu; Dongxia Yue (Landslides, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

DFT studies on pyrolysis mechanisms of tetrabromobisphenol A (TBBPA) - Jinbao Huang; Xin Mu; Xiaosong Luo; Hanxian Meng; Hong Wang; Li Jin; Xinsheng Li; Baosheng Lai (Environmental Science and Pollution Research, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Cytotoxic, clonal fidelity, and antioxidant evaluation of in vitro propagated Vitex negundo var. cannabifolia - Xue Meng; Fangfang Mu; Zeyu Zhang; Xinru Wu; Tiantian Gao; Fenglan Zhao; Jianping Xue; Yongbo Duan; Haijun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Deterioration effect of freeze-thaw on mechanical properties of roadbed clay under unfavorable conditions - Yiqiang Sun; Shangjiu Meng; Miao Wang; Hailong Mu; Xingchen Tang (Bulletin of Engineering Geology and the Environment, 2021)

Role of Wnt signaling pathways in type 2 diabetes mellitus - Jing Chen; Chong Ning; Jingjing Mu; Dongnan Li; Yan Ma; Xianjun Meng (Molecular and Cellular Biochemistry, 2021)

A global analysis of enemy release and its variation with latitude - Meng Xu; Xidong Mu; Shuang Zhang; Jaimie T. A. Dick; Bingtao Zhu; Dangen Gu; Yexin Yang; Du Luo; Yinchang Hu (Global Ecology and Biogeography, 2021)
Aim The enemy release hypothesis (ERH) posits that exotic species suffer less enemy damage than natives, which promotes their successful invasion. However, the generality of less damage for exotics remains widely debated. A recent view proposes that enemy release (ER) could change systematically with latitude, potentially helping to explain these inconsistencies. Here, we test whether exotic plant species suffer consistently lower herbivore damage relative to natives and whether ER varies with latitude. Location Global. Time period 1960–2018. Major taxa studied Plants. Methods Using leaf herbivory data for 1,098 plant species, we compared the herbivory rate between exotic and native plants across all taxa, between the introduced and native range of exotic species and between exotic and native species co‐occurring in the same community. We tested the interaction effect between origin (exotic versus native) and latitude to assess variation in ER with latitude. We also examined whether the effect of origin and its interaction with latitude changed with plant growth form (woody versus non‐woody). Finally, based on two ER effect‐size datasets, two meta‐regressions were performed to demonstrate the relationship between ER and latitude. Results Leaf herbivory rates were commonly lower for exotics than for natives. However, this differential herbivory rate was significant only for woody plants. No significant interactions were found between origin and latitude, indicating that ER did not change with latitude. The meta‐regressions also demonstrated that ER was not significantly correlated with latitude. Main conclusions The widespread lower herbivory rate for exotic compared with native woody plant species supports the ERH for exotic woody plants. Consistent ER with latitude indicates that ER should play a similar role regardless of latitude. One future challenge is to assess the extent to which ER in woody exotic plants translates to performance advantages and thereby influences their invasion success.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

Dual-Emitting N/S-Doped Carbon Dots-Based Ratiometric Fluorescent and Light Scattering Sensor for High Precision Detection of Fe(III) Ions - Zhiyan Chen; Xueqin Xu; Dongling Meng; Honglin Jiang; Yun Zhou; Shouai Feng; Zhao Mu; Yaling Yang (Journal of Fluorescence, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Influence Analysis of Mining’s Effect on Failure Characteristics of a Coal Seam Floor with Faults: A Numerical Simulation Case Study in the Zhaolou Coal Mine - Xiangxi Meng; Weitao Liu; Dianrui Mu (Mine Water and the Environment, 2018)

Scale effect and value criterion of the permeability of the interlayer staggered zones in the basalt of Jinsha River basin, China - Zhifang Zhou; Mu Lin; Qiaona Guo; Meng Chen (Hydrogeology Journal, 2018)

Tempo-spatial dynamics of water quality and its response to river flow in estuary of Taihu Lake based on GOCI imagery - Chenggong Du; Yunmei Li; Qiao Wang; Ge Liu; Zhubin Zheng; Meng Mu; Yuan Li (Environmental Science and Pollution Research, 2017)

Screening, purification, and characterization of a novel organic solvent-tolerant esterase, Lip2, from Monascus purpureus strain M7 - Li-Jing Kang; Zi-Tong Meng; Chen Hu; Yan Zhang; Hai-Lun Guo; Qing Li; Mu Li (Extremophiles, 2017)

The Role of Reelin Signaling in Alzheimer’s Disease - Nan-Nan Yu; Meng-Shan Tan; Jin-Tai Yu; An-Mu Xie; Lan Tan (Molecular Neurobiology, 2016)

Methyl jasmonate regulated diploid and tetraploid black locust (Robinia pseudoacacia L.) tolerance to salt stress - Mingquan Jiang; Fuling Xu; Mu Peng; Fenglan Huang; Fanjuan Meng (Acta Physiologiae Plantarum, 2016)

Molecular cloning, characterization and evolutionary analysis of vitellogenin in Chinese giant salamander Andrias davidianus - Hai-feng Tian; Yan Meng; Qiao-mu Hu; Han-bing Xiao (Biologia, 2015)

Isolation and detection of transcript-derived fragments (TDFs) in NaCl-stressed black locust (Robinia pseudoacacia L.) using cDNA-AFLP analysis - Fuling Xu; Mu Peng; Qiuxiang Luo; Mingquan Jiang; Xiuli Zhang; Xianchun Zong; Fanjuan Meng; Yajun Li (Acta Physiologiae Plantarum, 2015)

Enhanced organic phosphorus detection in sediments by foam separation and 31P-NMR - Yuxin Shi; Tengfei Pan; Di Mu; Hongqin Wu; Qingqiang Meng; Shuting Qi (Environmental Chemistry Letters, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

Molecular identification and interaction assay of the gene (OsUbc13) encoding a ubiquitin-conjugating enzyme in rice - Ya Wang; Meng-yun Xu; Jian-ping Liu; Mu-gui Wang; Hai-qing Yin; Ju-min Tu (Journal of Zhejiang University-SCIENCE B, 2014)

Gene cloning, expression and characterisation of a new β-agarase, AgWH50C, producing neoagarobiose from Agarivorans gilvus WH0801 - Nan Liu; Xiangzhao Mao; Meng Yang; Bozhong Mu; Dongzhi Wei (World Journal of Microbiology and Biotechnology, 2014)

Identification of microRNA-18a as a novel regulator of the insulin-like growth factor-1 in the proliferation and regeneration of deer antler - Wei Hu; Ting Li; Lei Wu; Mu Li; Xingyu Meng (Biotechnology Letters, 2014)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

The Role of Integrin αvβ8 in Neonatal Hypoxic-Ischemic Brain Injury - Jinhui Li; Yi Qu; Xihong Li; Deyuan Li; Fengyan Zhao; Meng Mao; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2010)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Magnification of Flood Disasters and its Relation to Regional Precipitation and Local Human Activities since the 1980s in Xinjiang, Northwestern China - Jiang Fengqing; Zhu Cheng; Mu Guijin; Hu Ruji; Meng Qingxia (Natural Hazards, 2005)